Treatment of early stage Supraglottic squamous cell carcinoma: meta-analysis comparing primary surgery versus primary radiotherapy - Krupal B. Patel; Anthony C. Nichols; Kevin Fung; John Yoo; S. Danielle MacNeil (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objectives For early stage supraglottic squamous cell carcinoma (SCC), single modality treatment either in the form of primary organ preservation surgery alone or radiation alone is recommended. Thus, a definite treatment strategy for early stage supraglottic SCC remains undefined. The primary objective of this study was to conduct a systematic review and meta-analysis comparing the oncologic outcomes of surgery and radiotherapy in early stage (Stage I and II) T1 N0 and T2 N0 supraglottic SCC. Methods Systematic methods were used to identify published and unpublished data. Two reviewers independently screened all titles, abstracts and articles for relevance using predefined criteria. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated. Results Five studies met the inclusion criteria for disease specific mortality with a total of 2864 pooled patients. 5-year disease specific mortality was lower in the surgery group (ORs 0.43, 95% CI 0.31–0.60). Four studies met the inclusion criteria for 5-year overall mortality with a total of 2790 pooled patients. Five-year overall mortality was lower in surgery group (ORs 0.40, 95% CI 0.29–0.55). Conclusions This is the first study to examine the management of early stage supraglottic SCC using meta-analytic methodology. Our results suggest that primary surgery may result in decreased disease specific and overall mortality compared to primary radiotherapy.